A review paper on the role of business continuity management in UAE public sector performance - Akmal, Suriati; Alblooshi, Abdulrahman Ahmed Mohammed Aldabal (Human Resource Management Academic Research Society, 2025)
In an era marked by volatility, uncertainty, complexity, and ambiguity (VUCA), Business Continuity Management (BCM) has become a critical strategic framework for public sector institutions, particularly in the United Arab Emirates (UAE). While BCM enhances organizational resilience, service continuity, and stakeholder confidence, gaps persist in its full integration within UAE government entities due to bureaucratic delays, fragmented implementation, and insufficient risk awareness. This study examines the relationship between BCM and organizational performance in the UAE public sector, identifying key factors such as top management communication, ICT tools, organizational structure, risk governance, employee training, and organizational culture. Through a comprehensive literature review, the research highlights the challenges and opportunities in BCM adoption, emphasizing the need for decentralized decision-making, digital readiness, and cultural adaptation. The findings contribute to theory by integrating organizational culture as a mediator in BCM effectiveness and offer practical insights for policymakers to strengthen continuity frameworks. Future research should explore sector-specific barriers, ICT tool efficacy, and culturally tailored BCM models to enhance resilience in the UAE’s rapidly evolving public sector.